TISSUE FLUORESCENCE IMAGING FOR QUICK NON-INVASIVE DIAGNOSIS IN ORAL AND MAXILLOFACIAL SURGERY - Nikolovski, Bruno; Radojkova, Vera Nikolovska; Dimova, Cena; Popovska, Mirjana; Ristovska, Stevica; Grezhlovska, Ana Belazelkovska; Popovik, Danica Monevska (Journal of Morphological Sciences; Vol 4 No 3 (2021): JMS, 2021)
Significant vital functions take place in the oral cavity and oropharynx, primarily mastication, as the initial function of the gastrointestinal system, swallowing, respiration and speech. All these vital biological functions can be endangered, ie aggravated, and even disabled by the appearance of neoplasms in that anatomical space. In the maxillofacial region, neoplasms can originate from a variety of tissues, from the mucous membranes of the oral cavity to the jaws, salivary glands, and even tumors of odontogenic origin. However, the most common tumor in the oral cavity is squamous cell carcinoma (OSSC), which originates from the oral mucosa. To determine the accuracy, sensitivity (Se) and specificity (Sp) of the Velscope screening method in the detection of premalignant and initial malignant lesions compared to the gold standard surgical biopsy. The study group consisted of 60 patients divided into two groups. The first group was formed by 30 patients with potentially malignant oral lesions (PML). Another 30 patients with preliminary diagnosis - oral cancer (OC) were included in the second group of examinees. The high sensitivity value of 92.86% and the accuracy of the method of 86.67% largely confirm the reliability and efficacy of the Velscope method in patients with highly suspected oral cancer lesions (OC), significantly more, comparing to the group of premalignant lesions. Key words : Velscope, oral cancer, premalignant lesions, tumor.  https://doi.org/10.55302/JMS2143001n